Advance in researches on relationship between human microbiome and lung cancer: a review - Jia-li CHEN; Shi-jie LI; Ming-lei ZHUO (Editorial Office of Chinese Journal of Public Health, 2023)
Lung cancer is one of the most common malignant tumors with poor prognosis and its incidence and mortality are maintained at a high level in China. In recent years with the development of next-generation sequencing, the studies on the correlation between microbiome and lung cancer and biomarkers have increased for providing references to early diagnosis and clinical treatment of lung cancer; some of the studies have indicated that lung cancer patients' microbiome of various body parts differ significantly from those of the healthy people and the changes in microbiome due to other respiratory diseases could affect the occurrence and development of lung cancer. In the paper, the studies on the relation between microbiome and lung cancer are reviewed; shortcomings of previous researches and prospects of future studies are also discussed.